2011
DOI: 10.1089/jpm.2010.0507
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Symptom Clusters: Clinical and Research Methodology

Abstract: Several important cancer SC have been identified. Nausea-vomiting, anxiety-depression, and dyspnea-cough clusters were consistently reported. The techniques of symptom cluster identification remain a research tool, but one with considerable potential clinical importance. Further research should validate our analytical techniques, and expand our knowledge about SC and their clinical importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 100 publications
6
100
2
4
Order By: Relevance
“…Following the challenge from the Symptom Management Research Group at the University of California, San Francisco, to the scientific community to consider the concept of a "symptom cluster" (17) and the publication of a state of the science lecture on symptom cluster research in oncology patients (18), a number of review articles have examined the conceptual and methodological issues associated with defining the characteristics of a symptom cluster (19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Three topics were the foci for the discussion of the "state of the science" in the area of defining characteristics of symptom clusters, namely conceptual issues, empiric identification of symptom clusters, and changes in symptom clusters over time.…”
Section: State Of the Sciencementioning
confidence: 99%
“…Following the challenge from the Symptom Management Research Group at the University of California, San Francisco, to the scientific community to consider the concept of a "symptom cluster" (17) and the publication of a state of the science lecture on symptom cluster research in oncology patients (18), a number of review articles have examined the conceptual and methodological issues associated with defining the characteristics of a symptom cluster (19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Three topics were the foci for the discussion of the "state of the science" in the area of defining characteristics of symptom clusters, namely conceptual issues, empiric identification of symptom clusters, and changes in symptom clusters over time.…”
Section: State Of the Sciencementioning
confidence: 99%
“…They were not able to correlate symptoms with disease stage or separate treatment related symptoms from cancer related symptoms (Kirkova et al, 2011a). However, a comprehensive clinical review of cancer symptom clusters showed that disease and treatment related symptoms are influenced by primary cancer site, disease stage and antitumor treatment (Kirkova et al, 2011b).…”
Section: Introductionmentioning
confidence: 96%
“…CRF is sometimes described as part of a cluster of symptoms together with anorexia, depression, and/or pain [6]. However, this is done mainly by cluster analysis of symptoms mentioned in literature, and clinical relevance has not yet been proven [6].…”
Section: Introductionmentioning
confidence: 99%